(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Systematic waste management is one of an important issue in present days due to improper waste disposal leads to high environmental risks. It is observed from the exploration that the best and the most feasible waste to energy technology is anaerobic digestion for organic and incineration for plastic waste. This study assesses the different waste-to-energy technologies based on the waste characteristics the emerging technologies are used to produce different by-products such as biogas, heat, electricity, fuel and compost and focus on environmental aspects of optimal disposal and management methods of waste and their compositions in different regions in India for Resource recovery. The waste to energy process should expand to all the regions to meet the sustainable development and energy problems with best practices